A Practical Assessment of the X-Ray Rooms Efficiency in Iraqi Hospitals Using a Detector and Radioactivity Level Sensor - Hamadi, Shahad Ibrahim Nawaf; Fayhan, Ahmed Majeed Saleh; Fayyad, Noor Al-Huda Ahmed Ayed; Nassar, Noor Subhi Abd al-Ghafour; Hassan, Duha Rahim Falih; Askar, Abdul Ghafour Mohammed Abdul Ghafoor (American Journal of Biodiversity, 2025)
The primary goal is to evaluate the efficiency of X-ray rooms, protect patients and examiners from leaking X-rays, and detect whether there is a leak of radiation and the extent of this leakage, if any. During our field visit to the hospitals in the city of Fallujah (F.T.H, A.G.H), all the dimensions of the X-ray rooms were measured, and it was found that all of them were designed according to the international standards for the dimensions of the rooms, as stipulated by the American National Standards Institute (ANSI), except for Al-Amriya General Hospital (Consultative), where it was found that the control room is located inside the examination room. The thickness of the lead was measured using a caliper (Vernier), and the shielding thickness of all radiology rooms was 2mm, which complies with ANSI international standards. The radiation leakage rate in X-ray rooms for all hospitals mentioned above was measured using a detector to sense the level of radioactivity. Low leakage rates were recorded at Fallujah Teaching Hospital (CR, DR), except for the door area of the CR room, where an average percentage of leakage was recorded. Therefore, there is a need to put warning signs of radiation in all leaked areas to alert auditors not to stand or sit in places of leakage. Everyone must be sufficiently aware to avoid exposure, so we urge the Ministry of Health and all concerned authorities to take action to find solutions to reduce the leakage rates that could lead, over time, to serious exposure for examiners.